Pengaruh praktik total quality management dan knowledge management terhadap kinerja perguruan tinggi - Gesit Thabrani; Ratih Ramadini (Jurnal Kajian Manajemen dan Wirausaha, 2021)
This study aims to analyze the impact of total quality management practice on higher education performance is mediated by knowledge management of universities in Padang City. This type of the research is a descriptive causative approach. This research was carried out in study program at universitie in Padang City. The populations in this study were all study programs throught universities, both state universities, private universities, religion universities, and university with many faculties in the city of Padang. The sample used is 80 study programs at university collages with Probability sampling technique with the sampling method is using stratified proportionate random sampling. The type of the data in this study are primary and secondary data. Data were collected through questionnaires, analyzed using the SPPS version 22 and path analysis.